What Is Beautiful Is Good and More Accurately Understood - Lorenzo, Genevieve L.; Biesanz, Jeremy C.; Human, Lauren J. (Psychological Science, 2010)
Beautiful people are seen more positively than others, but are they also seen more accurately? In a round-robin design in which previously unacquainted individuals met for 3 min, results were consistent with the “beautiful is good” stereotype: More physically attractive individuals were viewed with greater normative accuracy; that is, they were viewed more in line with the highly desirable normative profile. Notably, more physically attractive targets were viewed more in line with their unique self-reported personality traits, that is, with greater distinctive accuracy. Further analyses revealed that both positivity and accuracy were to some extent in the eye of the beholder: Perceivers’ idiosyncratic impressions of a target’s attractiveness were also positively related to the positivity and accuracy of impressions. Overall, people do judge a book by its cover, but a beautiful cover prompts a closer reading, leading more physically attractive people to be seen both more positively and more accurately.